Halal Marketplace: The Influence of Attitude, Subjective Norms, and Perceived Behavior Control on Purchase Intention of Muslim Consumers - Nasrul Fahmi Zaki Fuadi; Baidi Bukhori; Shovia Indah Firdiyanti (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Halal is currently a global concept that is becoming more universally recognized. Strengthening the digital economy is advocated by the 2019â€“2024 Indonesian Islamic Economic Masterplan (MEKSI), whose primary target is the halal market. Drawing in this issue, this study scrutinizes the influence of attitude, subjective norms, and perceived behavior controlÂ on the purchase intention of Muslim consumers in the halal marketplace. This study involves the Muslim community in Semarang, Indonesia. Taking a sample of 100 respondents, this quantitative study was used with multiple linear regression. The results demonstrated that Muslim consumers have a good understanding of the halal market. An individual's understanding of the halal market improves with increasing levels of education. Subjective norms and behavior control have a significant influence on the purchase intention of Muslim consumers in the halal marketplace. Attitude does not significantly influence Muslim consumers' purchase intentions in the halal marketplace. The outcomes of this research are anticipated to be helpful to Muslim consumers and entrepreneurs in encouraging competitiveness and sales so they may create a digital platform-based halal marketplace ecosystem in light of KNKS' expectations.